A battery
Patent Information
- Application Number
- CN202611259092.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-09
AI Technical Summary
传统胶纸(如丙烯酸胶带)通过物理覆盖保护活性涂层,防止掉粉和机械损伤,提高循环性能,但其不透锂离子的特性导致圆弧区离子传输受阻,显著降低能量密度
[0044]本发明提供一种电池,该电池保证圆弧区离子导通性的同时,抑制电解液断桥、紫斑形成以及高温副反应,具有优异的循环性能。通过在电极组件卷绕方向的正极弯折部中,于第一表面与相邻隔膜之间、第二表面与相邻隔膜之间中的至少一者设置包含多孔基材及其表面分散聚合物胶点胶层的绝缘件,不仅可以解决循环过程中正极活性颗粒掉粉导致的刺穿隔膜的情况,而且能够保障离子传导。然而电解液的过度浸润会导致绝缘件的粘性下降,使绝缘件在应力作用下发生分层剥离,导致电解液传输路径中断,为此结合包含氟磺酸锂和式1化合物的电解液,能够在保证弯折区电解液浸润和离子传输的基础上提高绝缘件与相邻界面的粘结稳定性,降低循环过程中分层及局部传输不连续的风险,进而减轻弯折区局部副反应并提升电池的循环稳定性和使用寿命。
Smart Images

Figure CN122889853A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary batteries, and more particularly to a battery. Background Technology
[0002] In wound batteries, the arc-shaped region of the positive electrode (including the electrode cutting edge and the tab bending area) becomes a key weak point in electrochemical performance and mechanical stability due to its special geometric structure. This region is subjected to significant mechanical and thermal stress during battery charging and discharging, and its poor electrolyte wettability makes it prone to forming localized hot spots and ion transport bottlenecks. This can lead to problems such as active material shedding and electrolyte breakage, ultimately causing battery performance degradation and safety hazards.
[0003] In existing technologies, the protection of the curved area of pouch lithium-ion batteries mainly relies on adhesive tape application technology. Traditional adhesive tape (such as acrylic tape) protects the active coating by physically covering it, preventing powder shedding and mechanical damage, and improving cycle performance. However, its lithium-ion impermeability hinders ion transport in the curved area, significantly reducing energy density.
[0004] Therefore, how to improve battery cycle life while ensuring ion conductivity in the arc region has become a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0005] This invention provides a battery that ensures ion conductivity in the arc region while suppressing electrolyte bridging, purple spot formation, and high-temperature side reactions, thus exhibiting excellent cycle performance.
[0006] This invention provides a battery comprising a positive electrode, a separator, a negative electrode, an insulating component, and an electrolyte, wherein the positive electrode, the separator, and the negative electrode are stacked and wound to form an electrode assembly;
[0007] The positive electrode includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector;
[0008] Along the winding direction of the electrode assembly, the electrode assembly includes a bending region, the bending region includes a plurality of positive electrode bending portions, at least one of the positive electrode bending portions is provided with the insulating member, along the thickness direction of the positive electrode sheet, the surface of the positive electrode bending portion near the winding center of the electrode assembly is a first surface, and the surface of the positive electrode bending portion away from the winding center of the electrode assembly is a second surface.
[0009] In the single positive electrode bend where the insulating element is provided, the insulating element is provided between the first surface and the adjacent diaphragm, and between the second surface and the adjacent diaphragm;
[0010] The insulating component includes a porous substrate and an adhesive layer located on at least one surface of the porous substrate, the adhesive layer comprising a plurality of dispersed polymer adhesive dots.
[0011] The electrolyte comprises lithium fluorosulfonate and a compound of formula 1:
[0012] Formula 1;
[0013] R1 and R2 are each independently selected from at least one of alkyl groups having 1-5 carbon atoms, alkenyl groups having 1-5 carbon atoms, and alkynyl groups having 1-5 carbon atoms, whether halogenated or unsubstituted.
[0014] In the battery described above, the dispersion coefficient of the adhesive layer is A, where A is 0.2~1.5;
[0015] The dispersion coefficient of the adhesive layer refers to the ratio of the coverage of polymer adhesive dots per square millimeter to the number of polymer adhesive dots per square millimeter.
[0016] In the battery described above, based on the electrolyte, the mass percentage of lithium fluorosulfonate is B.
[0017] K = B / A, where K is between 0.2 and 5.0.
[0018] In the battery described above, the coverage of the polymer adhesive dots within a square millimeter area is 10% to 60%;
[0019] And / or, the number of polymer adhesive dots per square millimeter of the insulating element is 5 to 60;
[0020] And / or, the porosity of the porous substrate is 25% to 70%.
[0021] In the battery described above, the electrolyte satisfies at least one of the following conditions:
[0022] (1) Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, where B is 0.5%~5%;
[0023] (2) Based on the electrolyte, the mass percentage of the compound of formula 1 is C, where C is 2% to 10%;
[0024] (3) Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, the mass percentage of the compound of formula 1 is C, R=C / B, and R is 0.5~10.
[0025] The battery described above, wherein the compound of Formula 1 includes at least one of the compounds with chemical formulas as shown in Formulas 1-1 to 1-7:
[0026] Equation 1-1, Equation 1-2, Equation 1-3,
[0027] Equation 1-4, Equations 1-5 Equations 1-6
[0028] Equations 1-7.
[0029] As described above, in the battery, at least a portion of the first surface includes a first region, at least a portion of the first region is covered by the insulating member, and the first region is provided with a first linear recessed structure.
[0030] The first linear recessed structure satisfies at least one of the following conditions:
[0031] (1) The average width of the opening end of the first linear recessed structure is 50 μm to 150 μm;
[0032] (2) The distance between adjacent first linear recessed structures is 100μm~350μm;
[0033] (3) The thickness of the positive electrode active layer is H1, the average depth of the first linear recess structure is independently H2, and H2 / H1 is 0.1~0.6; preferably, H1 is 50μm~150μm and H2 is 5μm~50μm;
[0034] (4) Along the width direction of the positive electrode, the size of the first region is equal to the width of the positive electrode.
[0035] As described above, in the battery, at least a portion of the second surface includes a second region, at least a portion of the second region is covered by the insulating member, and the second region is provided with a second linear recessed structure;
[0036] The second linear recessed structure satisfies at least one of the following conditions:
[0037] (1) The average width of the opening end of the second linear recessed structure is 50 μm to 150 μm;
[0038] (2) The distance between adjacent second linear concave structures is 100μm~350μm;
[0039] (3) The thickness of the positive electrode active layer is H1, the average depth of the second linear recess structure is H3, and the ratio of H3 to H1 is 0.1 to 0.6; preferably, H1 is 50 μm to 150 μm and H3 is 5 μm to 50 μm.
[0040] (4) Along the width direction of the positive electrode, the size of the second region is equal to the width of the positive electrode.
[0041] In the battery described above, the separator includes a separator substrate and polymer particles disposed on at least a portion of the surface of the separator substrate.
[0042] In the battery described above, the average particle size of the polymer particles is 0.3 μm to 3 μm;
[0043] And / or, the polymer particles include at least one of acrylate polymers and fluoropolymers, wherein the acrylate polymers do not contain fluorine.
[0044] This invention provides a battery that, while ensuring ion conductivity in the arc region, suppresses electrolyte bridging, purple spot formation, and high-temperature side reactions, exhibiting excellent cycle performance. By providing an insulating component comprising a porous substrate and a polymer dot layer dispersed on its surface between at least one of the first surface and an adjacent separator, or between the second surface and an adjacent separator, in the positive electrode bend of the electrode assembly winding direction, not only can the problem of separator puncture caused by positive electrode active particle shedding during cycling be solved, but ion conduction can also be guaranteed. However, excessive electrolyte wetting can lead to a decrease in the adhesiveness of the insulating component, causing delamination and peeling under stress, resulting in interruption of the electrolyte transport path. Therefore, by combining an electrolyte containing lithium fluorosulfonate and a compound of formula 1, the adhesion stability between the insulating component and adjacent interfaces can be improved while ensuring electrolyte wetting and ion transport in the bend region. This reduces the risk of delamination and local transport discontinuity during cycling, thereby mitigating local side reactions in the bend region and improving the cycle stability and lifespan of the battery. Attached Figure Description
[0045] Figure 1 This is a schematic diagram of the structure of an electrode assembly provided in a specific embodiment of the present invention;
[0046] Figure 2 This is a partial structural schematic diagram of the positive electrode sheet provided in a specific embodiment of the present invention;
[0047] Figure 3 This is a partial structural schematic diagram of the positive electrode sheet provided in a specific embodiment of the present invention.
[0048] Explanation of reference numerals in the attached figures:
[0049] 01-Insulator; 02-Positive electrode sheet; 21-First linear recessed structure; A-First surface; A1-Positive electrode bending portion. Detailed Implementation
[0050] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples of apparatuses and methods consistent with some aspects of the invention as detailed in the appended claims.
[0051] In existing technologies, the protection of the active layer in the bending area of the positive electrode is typically achieved by covering the corresponding area with adhesive tape or a separator-like insulating material. This covers the surface of the bending section to reduce the risk of powder shedding, wear, and localized short circuits caused by cutting edges and winding bends. This type of solution mainly relies on the physical isolation effect of the insulating material to maintain structural integrity and utilizes the porosity or surface properties of the material itself to improve electrolyte penetration and ion transport in this area.
[0052] However, traditional adhesive tapes often have a dense structure, which can weaken the continuity of ion channels in the bending section of the positive electrode after covering it, leading to increased local polarization. Although separator-type adhesive tapes with certain lithium-ion channels can improve wettability to some extent, the adhesive strength of the adhesive layer is prone to weakening under long-term electrolyte wetting and charge-discharge cycle stress. Especially near the edges of the first or second surface in the bending area, it is more likely to lift, delaminate, or detach locally, resulting in purple spots on the negative electrode corresponding to the edge area of the adhesive application.
[0053] The inventors believe that multi-dimensional collaborative optimization can solve the problems of ion conductivity, bonding stability, electrolyte bridging, and suppression of high-temperature decomposition side reactions in the arc region of the positive electrode of soft-pack lithium-ion batteries.
[0054] Based on this, the present invention provides a battery including a positive electrode, a separator, a negative electrode, an insulating component and an electrolyte, wherein the positive electrode, the separator and the negative electrode are stacked and wound to form an electrode assembly.
[0055] The positive electrode includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector;
[0056] Along the winding direction of the electrode assembly, the electrode assembly includes a bending region, the bending region includes a plurality of positive electrode bending portions, at least one positive electrode bending portion is provided with an insulating member, and along the thickness direction of the positive electrode sheet, the surface of the positive electrode bending portion near the winding center of the electrode assembly is a first surface, and the surface of the positive electrode bending portion away from the winding center of the electrode assembly is a second surface.
[0057] In a single positive electrode bend provided with an insulating element, at least one of the first surface and the adjacent diaphragm, and the second surface and the adjacent diaphragm, is provided with an insulating element.
[0058] The insulating component includes a porous substrate and an adhesive layer located on at least one surface of the porous substrate, the adhesive layer comprising a plurality of dispersed polymer adhesive dots.
[0059] The electrolyte comprises lithium fluorosulfonate and a compound of formula 1:
[0060] Formula 1;
[0061] R1 and R2 are each independently selected from at least one of alkyl groups having 1-5 carbon atoms, alkenyl groups having 1-5 carbon atoms, and alkynyl groups having 1-5 carbon atoms, whether halogenated or unsubstituted.
[0062] The electrode assembly in this invention can be formed using a winding structure commonly used in soft-pack lithium-ion batteries. Specifically, positive electrode sheets, separators, and negative electrode sheets can be prepared first, and then stacked and wound into a core in the order of positive electrode sheet / separator / negative electrode sheet / separator.
[0063] Commonly used positive electrode current collectors in this field can be selected, such as aluminum foil. The positive electrode active layer can be disposed on one or both sides of the positive electrode current collector, and the positive electrode active layer can contain positive electrode active material, conductive agent and binder.
[0064] The negative electrode can be made of copper foil current collector and its surface negative electrode active layer.
[0065] The diaphragm can be any commonly used diaphragm material in this field.
[0066] like Figure 1 As shown, after winding, a bending zone is formed at the arc transition position. The positive electrode bending part A1 in the bending zone is prone to become a local interface instability area due to the superposition of cutting edge, active layer bending stress and interlayer clamping force. Therefore, an insulating component 01 is introduced in this area.
[0067] At least one positive electrode bend is provided with an insulating element, indicating that the number of insulating elements can be set according to factors such as the length of the bend area, the number of winding turns, and the local stress concentration in the width direction of the positive electrode sheet. When the bend area is short, a single insulating element can be set accordingly. When the bend area has a large extension length or multiple positive electrode bends have similar stress areas, multiple insulating elements can also be set. Multiple insulating elements can be arranged at intervals along the winding direction or continuously in adjacent sections, so that the parts in the bend area that are more sensitive to stress and wetting are all in a protected state.
[0068] The first surface refers to the surface of the positive electrode bend facing the winding center, and the second surface refers to the surface away from the winding center. The insulating element can be disposed between the first surface and the adjacent diaphragm, between the second surface and the adjacent diaphragm, or simultaneously on both sides.
[0069] In one possible embodiment, in a single positive electrode bending section provided with an insulating element, an insulating element is provided between the first surface and the adjacent separator, and an insulating element is also provided between the second surface and the adjacent separator, thereby forming an interface buffer and insulating protective layer on both sides of the positive electrode bending section, making the contact between the positive electrode active layer and the adjacent separator more stable.
[0070] In another possible implementation, an insulating element is provided only between the first surface and the adjacent diaphragm, or only between the second surface and the adjacent diaphragm. In this case, the selection can be made by combining the winding tension, bending radius, local temperature rise distribution and encapsulation space, so that the protective structure preferentially acts on the side that is more prone to active layer wear, interface warping or uneven wetting.
[0071] The insulating component adopts a composite structure of a porous substrate and an adhesive layer. The porous substrate can be any one of polyethylene, polypropylene, polyimide, or polyethylene terephthalate, or a composite porous membrane formed by two or more of these materials, or other polymer microporous membranes with ion permeability.
[0072] The porous structure of the porous substrate can provide channels for electrolyte penetration and storage, so that after it covers the bending part of the positive electrode, it does not form a completely dense closed interface, but forms a continuous lithium-ion transport channel, so that lithium ions can continue to migrate through the electrolyte phase within the area covered by the insulating component.
[0073] The adhesive layer is located on at least one side of the porous substrate, meaning it can be a single-sided or double-sided adhesive structure. With single-sided adhesive, the adhesive surface can be positioned towards the positive electrode bend or the adjacent separator to fix the main adhesion interface. With double-sided adhesive, the two sides of the porous substrate form adhesion interfaces with the positive electrode bend and the adjacent separator, respectively, further enhancing interlayer constraint.
[0074] Unlike traditional continuous dense adhesive layers, the adhesive layer in this application comprises several dispersed polymer adhesive dots. That is, the adhesive layer does not completely and continuously seal the surface of the porous substrate, but rather forms multiple spaced-apart bonding units on the surface. Pore areas or fluid passages are preserved between the polymer adhesive dots. This structure achieves the coexistence of localized bonding and non-bonding channels, allowing the insulating component to provide sufficient initial adhesion and wet adhesion retention after cycling when in contact with the positive electrode active layer and adjacent separators. Simultaneously, it preserves the open paths required for electrolyte wetting and ion migration.
[0075] Polymer adhesive dots may include adhesives commonly used in the art, such as at least one of rubber adhesives, acrylate adhesives, acrylic adhesives, and polyolefin adhesives.
[0076] The electrolyte is a non-aqueous electrolyte system, comprising lithium fluorosulfonate and a compound of formula 1, and other components may be conventional electrolyte components in the art.
[0077] In the compound of Formula 1, R1 and R2 are each independently selected from at least one of alkyl, alkenyl, and alkynyl groups having 1 to 5 carbon atoms, whether halogenated or unsubstituted.
[0078] The presence of 1 to 5 carbon atoms in the substituents indicates that the substituents have a small molecular volume and moderate electronic effects, enabling them to maintain a good solubility and dispersion in the electrolyte and participate in interfacial reactions; halogen substitution can further regulate the electron attraction characteristics and redox reactivity of the molecule.
[0079] For example, R1 and R2 can be any one of methyl, ethyl, propyl, butyl, pentyl, vinyl, propenyl, ethynyl, and propynyl, and R1 and R2 can be the same or different. By setting short-chain alkyl, alkenyl, or alkynyl substituents, the compound of formula 1 is more likely to participate in the formation of a stable interface layer in the environment of higher local interfacial energy in the bending region. When combined with lithium fluorosulfonate, it can adjust the electrolyte decomposition path at the bending part of the positive electrode and the interface of the adjacent separator, so that the formed interface film is more uniformly attached to the exposed edge of the active layer, the area near the polymer glue dots, and the vicinity of the pores of the porous substrate.
[0080] The battery provided by this invention stabilizes the interface of the bending region through the synergy of a porous substrate, dispersed polymer dots, and a specific electrolyte system. Specifically, when the positive electrode bending section is subjected to alternating mechanical stress during winding and cycling, the porous substrate provides compliant support and an electrical insulation barrier. The dispersed polymer dots form fixed nodes at several discrete locations, suppressing the tendency of the insulating component to de-adhede across the entire surface under long-term electrolyte wetting, while retaining the open pores between the polymer dots as channels for electrolyte wetting and lithium ion migration. Lithium fluorosulfonate and the compound of Formula 1 in the electrolyte further enter the interface of the bending region through these channels. Through interfacial film formation and side reaction regulation, a relatively stable chemical environment is formed at the edge of the positive electrode active layer, the contact area of the insulating component, and the surface of adjacent separators. Through this process, the local ion transport interruption that was originally prone to occur in the bending area due to the continuous coverage of the adhesive layer is transformed into an interface structure with multi-path penetration characteristics. The risk of lifting and delamination that was originally prone to occur due to wet adhesion attenuation is jointly suppressed by the local anchoring effect of the dispersed polymer adhesive dots and the stable interface formed by the electrolyte additives. Thus, the transport continuity and adhesion stability of the bending area during the cycle are taken into account, thereby ensuring that the battery maintains a relatively uniform local reaction state under long-term charge and discharge conditions.
[0081] In some embodiments of the present invention, the dispersion coefficient of the adhesive layer is A, where A is 0.2 to 1.5;
[0082] The dispersion coefficient of an adhesive layer refers to the ratio of the coverage of polymer adhesive dots per square millimeter to the number of polymer adhesive dots per square millimeter.
[0083] The coverage rate of polymer adhesive dots refers to the percentage of area covered by polymer adhesive dots per square millimeter based on a porous base film. The distribution of polymer adhesive dots on the surface of the insulating component can be first acquired using microscopic images. Then, image processing software is used to count the projected area of the polymer adhesive dots and calculate the coverage rate. Simultaneously, the number of polymer adhesive dots within the same observation area is counted, and then substituted into the above formula to obtain the dispersion coefficient A value of the adhesive layer.
[0084] It should be noted that the coverage rate of polymer adhesive dots per square millimeter and the number of polymer adhesive dots per square millimeter are only used to calculate the dispersion coefficient A. For example, when the coverage rate of polymer adhesive dots per square millimeter is 20% and the number of polymer adhesive dots per square millimeter is 40, the dispersion coefficient A is 20 / 40 = 0.5.
[0085] In detail, the dispersion coefficient A of the adhesive layer includes, but is not limited to, a range of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or any two of these.
[0086] A small value usually means that the polymer adhesive dots are too sparse, which can easily lead to insufficient local adhesion, lifting, or delamination; a large value indicates that the polymer adhesive dots are too concentrated, which can easily form local dense areas, affecting electrolyte penetration and increasing interfacial resistance.
[0087] Controlling the dispersion coefficient of the polymer adhesive dots within the aforementioned range allows for a fine and uniform distribution of the dots. This serves several purposes: firstly, it evenly distributes interfacial stress across the dots, effectively mitigating or even eliminating the risk of localized stress concentration, thus improving or suppressing localized debonding caused by stress concentration; secondly, it increases the number of bonding sites at the edges of the insulating component that can adhere to the positive electrode, thereby improving the long-term stability of the adhesion between the edge of the insulating component and the positive electrode in the bending area, further mitigating or suppressing the risk of debonding at the edge of the insulating component; and thirdly, the fine and uniform dot distribution improves the uniformity of ion permeation, reducing the risk of severe lithium plating at the edge due to uneven lithium ion concentration. Finally, the fine and uniform dot distribution improves the uniformity of electrolyte distribution between the positive electrode and the insulating component, homogenizing the lithium ion flux and eliminating localized overpotential, thus mitigating or even eliminating the problem of localized electrolyte bridging and reducing the risk of purple spots.
[0088] In some embodiments of the present invention, based on the electrolyte, the mass percentage of lithium fluorosulfonate is B.
[0089] K = B / A, where K is between 0.2 and 5.0.
[0090] It should be noted that the mass percentage of lithium fluorosulfonate B is only used to calculate the K value. For example, in some embodiments, the mass percentage of lithium fluorosulfonate is 2%, A is 1, and K=2 / 1=2.
[0091] In detail, K includes, but is not limited to, a range of 0.2, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, or any two of these.
[0092] When the K value is too low, lithium fluorosulfonate has a limited effect on improving broken bridges. Even if the adhesive layer is uniform, it cannot maintain the continuity of ion channels, and purple spots are aggravated. When the K value is too high, the risk of decomposition of lithium fluorosulfonate increases significantly. Especially when the dispersion coefficient deviates from the appropriate level, resulting in local heat accumulation, the high-temperature performance deteriorates.
[0093] By setting K=B / A and controlling K within the range of 0.2~5.0, the chemical regulation capability of lithium fluorosulfonate in the electrolyte is matched with the dispersion structure of the insulating adhesive layer. This not only forms a more stable interfacial wetting and ion transport environment in the bending zone, but also suppresses interfacial side reactions caused by insufficient additives. It also avoids the increase in interfacial impedance and adhesion degradation caused by excessive lithium fluorosulfonate or unbalanced adhesive layer distribution. After the two are coupled and constrained by the ratio K, the insulation protection, ion conduction and interfacial adhesion stability near the first or second surface of the bending zone can be optimized simultaneously, thereby improving the reliability during cycling and extending the cycle life.
[0094] In some embodiments of the present invention, the coverage of polymer adhesive dots in an area of 10% to 60% is achieved.
[0095] In detail, the coverage of polymer adhesive dots in an area of square millimeters includes, but is not limited to, a range of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any combination thereof.
[0096] By controlling the coverage of polymer adhesive dots per square millimeter on the insulating component to 10%–60%, sufficient adhesion area can be formed in the bending region. This avoids insufficient adhesion and increased risk of lifting due to too low coverage, while also preventing pore blockage and ion transport obstruction due to too high coverage. The mechanism is that the dispersed polymer adhesive dots contact the positive electrode bending section and adjacent membranes in a dotted manner, providing interfacial adhesion while maintaining a continuous electrolyte penetration path.
[0097] In some embodiments of the present invention, the number of polymer adhesive dots per square millimeter area of the insulating element is 5 to 60.
[0098] Specifically, the number of polymer adhesive dots per square millimeter of the insulating element includes, but is not limited to, a range of 5, 10, 20, 30, 40, 50, 60, or any combination thereof.
[0099] If the number of polymer adhesive dots is too small, the bonding will be uneven; if the number of polymer adhesive dots is too large, the dots will easily merge together, weakening the liquid permeability and reducing the adhesive strength of individual dots. The number of polymer adhesive dots per square millimeter of the insulating component should be controlled between 5 and 60. The distribution density and size of the polymer adhesive dots can be further adjusted to ensure that the number and size of the adhesive dots per unit area are appropriate, thereby suppressing local stress concentration and reducing the probability of interfacial delamination.
[0100] In some embodiments of the present invention, the porosity of the porous substrate is 25% to 70%.
[0101] The porosity of porous substrates can be measured using methods known in the art. One method is described here: a porous substrate sample is weighed, immersed in n-butanol solvent for 2 hours, removed, the surface liquid is wiped off, and the sample is weighed. The porosity is calculated using the following formula:
[0102]
[0103] Where W2 is the weight of the porous substrate sample after immersion in n-butanol, in g; W1 is the weight of the porous substrate before immersion, in g; and A is the area of the porous substrate sample, in cm². 2 ; d is the average thickness of the porous substrate sample in cm; ρ is the density of n-butanol, 0.811 g / mL.
[0104] In detail, the porosity of the porous substrate includes, but is not limited to, a range of 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or any combination thereof.
[0105] The porosity of porous substrates is controlled between 25% and 70%, which allows the substrate to have both good supporting strength and ion passage capacity. If the porosity is too low, it will restrict electrolyte wetting and increase impedance. If the porosity is too high, it will weaken its protection of the positive electrode active layer. For example, it may be punctured by falling active particles, resulting in local damage to the membrane.
[0106] In some embodiments of the present invention, the electrolyte satisfies at least one of the following conditions:
[0107] (1) Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, and B is 0.5%~5%;
[0108] (2) Based on the electrolyte, the mass percentage of compound 1 is C, where C is 2%~10%;
[0109] (3) Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, the mass percentage of compound 1 is C, R=C / B, and R is 0.5~10.
[0110] For condition (1), based on the electrolyte, the mass percentage B of lithium fluorosulfonate is including but not limited to 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% or any combination thereof.
[0111] Introducing lithium fluorosulfonate as a functional lithium salt into the electrolyte, its anions have a large volume and good delocalization characteristics, which helps maintain the continuity of the electrolyte during the cycling process, improves the bridging phenomenon, and can preferentially participate in the interfacial reaction during the charge and discharge process to form a more stable fluorine-rich protective layer, maintaining the continuity of ion transport at the solid-liquid interface, thereby suppressing the bridging phenomenon. Controlling its mass percentage B at 0.5%~5% can achieve a balance between interfacial film-forming ability and electrolyte bulk ion conduction. Too low a content will result in insufficient protection, while too high a content may increase viscosity and induce side reactions.
[0112] For condition (2), based on the electrolyte, the mass percentage B of compound of formula 1 includes, but is not limited to, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof.
[0113] Adding a compound of formula 1 to the electrolyte allows the amino groups in its molecule to capture acidic decomposition products, while the sulfonyl fluoride groups help form a dense film at the positive and negative electrode interfaces, thereby reducing continuous decomposition and gas generation. Controlling its mass percentage (C) to 2%–10% ensures sufficient interfacial regulation capability while avoiding impedance increases due to excessive addition.
[0114] For condition (3), based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, the mass percentage of compound 1 is C, R = C / B, and R is 0.5~10.
[0115] In detail, R includes, but is not limited to, a range of 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any two of these ranges.
[0116] Lithium fluorosulfonate anions have a large volume and good delocalization characteristics, maintaining electrolyte continuity and ion transport channels in the bending region and improving bridging phenomena. Compound of Formula 1 focuses on stabilizing the electrolyte chemical environment. When the two are combined in the above ratio, the interfacial film formation rate can be matched with the film density, avoiding film embrittlement, local deposition, or insufficient protection caused by excessively strong or weak single components. By controlling R between 0.5 and 10, the ion channel maintenance capacity in the bending region can be matched with the chemical stability of the electrolyte, further improving interfacial stability during high-temperature storage and cycling, thereby reducing side reactions, slowing down impedance growth, and extending battery life.
[0117] In some embodiments of the present invention, the compound of Formula 1 includes at least one of the compounds with chemical formulas as shown in Formulas 1-1 to 1-7:
[0118] Equation 1-1, Equation 1-2, Equation 1-3,
[0119] Equation 1-4, Equations 1-5 Equations 1-6
[0120] Equations 1-7.
[0121] By limiting the compound of Formula 1 to at least one of the above seven types of structures, it is possible to enhance the protection of the positive electrode bending region and its adjacent interface while maintaining ion conductivity, thereby avoiding interfacial film embrittlement or uneven deposition.
[0122] In some embodiments of the present invention, such as Figure 2 As shown, at least a portion of the first surface A includes a first region, at least a portion of the first region is covered by an insulating member 01, and the first region is provided with a first linear recessed structure 21.
[0123] The first linear concave structure 21 satisfies at least one of the following conditions:
[0124] (1) The average width of the opening end of the first linear concave structure 21 is 50μm~150μm;
[0125] (2) The distance between adjacent first linear concave structures 21 is 100μm~350μm;
[0126] (3) The thickness of the positive electrode active layer 02 is H1, and the average depth of the first linear recessed structure 21 is independently H2, with H2 / H1 being 0.1-0.6; preferably, H1 is 50μm~150μm and H2 is 5μm~50μm;
[0127] (4) such as Figure 3 As shown, along the width direction of the positive electrode, the size of the first region is equal to the width of the positive electrode O2.
[0128] That is, the surface of the positive electrode bending portion near the winding center includes a first region with a first linear recessed structure, and at least part of the first region is covered by an insulating member.
[0129] In some embodiments, the first surface of the partial positive electrode bending portion includes a first region, that is, the first surface of the partial positive electrode bending portion is provided with a first linear recess structure, and the first surface of the partial positive electrode bending portion is not provided with a first linear recess structure.
[0130] In some other embodiments, a portion of the first surface of any positive electrode bend includes a first region, that is, a portion of the first surface of a single positive electrode bend is a first region, and this portion is provided with a first linear recess structure.
[0131] In some other embodiments, the first surface of the positive electrode bending portion has multiple first regions with a first linear recessed structure, wherein some of the first regions are covered by an insulating element and some of the first regions are not covered by an insulating element.
[0132] In some other embodiments, a portion of the surface of any first region in the first surface of the positive electrode bend is covered by an insulating element. That is, in a single first region having a first linear recessed structure, a portion of the region having the first linear recessed structure is covered by an insulating element, while a portion of the region having the first linear recessed structure is not covered by an insulating element.
[0133] For condition (1), the average width of the opening segment of the first linear recessed structure includes, but is not limited to, a range of 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or any two of these.
[0134] By controlling the average width of the opening end to 50μm~150μm, an appropriate space for accommodating and guiding the flow can be formed when the insulating component is attached. This facilitates the embedding of the adhesive layer or porous substrate into the recess, while avoiding excessive width that would reduce the structural strength.
[0135] For condition (2), the distance between adjacent first linear concave structures includes, but is not limited to, a range of 100μm, 120μm, 140μm, 160μm, 180μm, 200μm, 220μm, 240μm, 260μm, 280μm, 300μm, 320μm, 340μm, 350μm or any two of these.
[0136] When the distance between adjacent first linear depression structures is set to 100μm~350μm, multiple depressions can be evenly arranged along the width direction to form a continuous but not excessively dense buffer and channel network, thereby taking into account both mechanical support and ion transport.
[0137] For condition (3), the thickness of the positive electrode active layer is H1, the average depth of the first linear recess structure is independently H2, and H2 / H1 is 0.1~0.6; preferably, H1 is 50μm~150μm and H2 is 5μm~50μm.
[0138] In detail, H2 / H1 includes, but is not limited to, a range of 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, or any two of these ranges.
[0139] Preferably, H1 includes, but is not limited to, a range of 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or any combination thereof; H2 includes, but is not limited to, a range of 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any combination thereof.
[0140] If the average depth H2 and the active layer thickness H1 satisfy H2 / H1 = 0.1~0.6, and preferably H1 = 50μm~150μm and H2 = 5μm~50μm, then the depression can provide sufficient interface volume and locking depth without weakening the overall load-bearing capacity of the positive electrode active layer. The controlled shallow depression structure reduces local stress concentration and enhances the adhesion stability of the insulating component.
[0141] For condition (4), along the width direction of the positive electrode, the size of the first region is equal to the width of the positive electrode.
[0142] When the dimension of the first region along the width of the positive electrode is equal to the width of the positive electrode, the recessed structure can cover the entire bending area, so that insulation coverage and wetting improvement are achieved simultaneously on the entire electrode, thereby improving the interface consistency of the bending area, suppressing warping and delamination, and thus ensuring the continuity of ion transport, structural reliability and battery life during cycling.
[0143] In some embodiments of the present invention, at least a portion of the second surface includes a second region, at least a portion of the second region is covered by an insulating element, and the second region is provided with a second linear recessed structure.
[0144] The second linear concave structure satisfies at least one of the following conditions:
[0145] (1) The average width of the opening end of the second linear concave structure is 50 μm to 150 μm;
[0146] (2) The distance between adjacent second linear depression structures is 100μm~350μm;
[0147] (3) The thickness of the positive electrode active layer is H1, the average depth of the second linear recess structure is H3, and the ratio of H3 to H1 is 0.1 to 0.6; preferably, H1 is 50 μm to 150 μm and H3 is 5 μm to 50 μm.
[0148] (4) Along the width direction of the positive electrode, the size of the second region is equal to the width of the positive electrode.
[0149] That is, the side surface of the positive electrode bending portion away from the winding center includes a second region with a second linear recessed structure, and at least part of the second region is covered by an insulating member.
[0150] In some embodiments, the second surface of the partial positive electrode bending portion includes a second region, that is, the second surface of the partial positive electrode bending portion is provided with a second linear recess structure, and the second surface of the partial positive electrode bending portion is not provided with a second linear recess structure.
[0151] In some other embodiments, a portion of the second surface of any positive electrode bend includes a second region, that is, a portion of the second surface of a single positive electrode bend is a second region, and this portion is provided with a second linear recess structure.
[0152] In some other embodiments, the second surface of the positive electrode bending portion has a plurality of second regions with a second linear recessed structure, wherein some of the second regions are covered by an insulating element and some of the second regions are not covered by an insulating element.
[0153] In some other embodiments, a portion of the surface of any second region in the second surface of the positive electrode bend is covered by an insulating element. That is, in a single second region having a second linear recess structure, a portion of the region having the second linear recess structure is covered by an insulating element, while a portion of the region having the second linear recess structure is not covered by an insulating element.
[0154] For condition (1), the average width of the opening segment of the second linear recessed structure includes, but is not limited to, a range of 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or any two of these.
[0155] By controlling the average width of the opening end to 50μm~150μm, an appropriate space for accommodating and guiding the flow can be formed when the insulating component is attached. This facilitates the embedding of the adhesive layer or porous substrate into the recess, while avoiding excessive width that would reduce the structural strength.
[0156] For condition (2), the distance between adjacent second linear concave structures includes, but is not limited to, a range of 100μm, 120μm, 140μm, 160μm, 180μm, 200μm, 220μm, 240μm, 260μm, 280μm, 300μm, 320μm, 340μm, 350μm or any two of these.
[0157] When the distance between adjacent second linear depression structures is set to 100μm~350μm, multiple depressions can be evenly arranged along the width direction to form a continuous but not overly dense buffer and channel network, thus taking into account both mechanical support and ion transport.
[0158] For condition (3), the thickness of the positive electrode active layer is H1, the average depth of the second linear recess structure is independently H3, and H3 / H1 is 0.1~0.6; preferably, H1 is 50μm~150μm and H3 is 5μm~50μm.
[0159] In detail, H2 / H1 includes, but is not limited to, a range of 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, or any two of these ranges.
[0160] Preferably, H1 includes, but is not limited to, a range of 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm or any combination thereof; H3 includes, but is not limited to, a range of 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm or any combination thereof.
[0161] If the average depth H3 and the active layer thickness H1 satisfy H2 / H1 = 0.1~0.6, and preferably H1 = 50μm~150μm and H3 = 5μm~50μm, then the depression can provide sufficient interface volume and locking depth without weakening the overall load-bearing capacity of the positive electrode active layer. The controlled shallow depression structure reduces local stress concentration and enhances the adhesion stability of the insulating component.
[0162] For condition (4), along the width direction of the positive electrode, the size of the second region is equal to the width of the positive electrode.
[0163] When the dimension of the second region along the width of the positive electrode is equal to the width of the positive electrode, the recessed structure can cover the entire bending area, so that insulation coverage and wetting improvement are achieved simultaneously on the entire electrode, thereby improving the interface consistency of the bending area, suppressing warping and delamination, and thus ensuring the continuity of ion transport, structural reliability and battery life during cycling.
[0164] In some embodiments of the present invention, the diaphragm includes a diaphragm substrate and polymer particles disposed on at least a portion of the surface of the diaphragm substrate.
[0165] The diaphragm substrate includes a base membrane, which provides basic isolation between electrodes and ion channel support. It is preferably a porous polyolefin base membrane, such as polyethylene, polypropylene, or a composite base membrane thereof, to balance mechanical strength and electrolyte wettability.
[0166] Polymer particles are disposed on at least a portion of the surface of the membrane substrate, and may cover one side, two sides, or a local area.
[0167] Polymer particles increase the surface roughness of the separator, forming a micro-protrusion structure. This creates gaps at the separator-electrode interface, enhancing the electrolyte wetting rate and storage capacity in the arc-shaped region. Furthermore, these gaps form heat dissipation channels, promoting heat removal and reducing local temperature peaks in the arc-shaped region. By improving heat dissipation and lowering local temperatures, the driving force for the thermal decomposition of lithium fluorosulfonate is reduced thermodynamically. Simultaneously, the uniform electrolyte distribution prevents excessively high local concentrations of lithium fluorosulfonate, further suppressing decomposition side reactions and improving high-temperature stability.
[0168] In some embodiments of the present invention, the average particle size of the polymer particles is 0.3 μm to 3 μm.
[0169] In detail, the average particle size of the polymer particles includes, but is not limited to, a range of 0.3 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, or any combination thereof.
[0170] When the polymer particles have a suitable particle size, the gap between the diaphragm and the electrode interface can be appropriate, avoiding the formation of broken bridges due to electrolyte consumption in the later stages of cycling. In addition, the polymer particles reduce the actual contact area between the insulator and the diaphragm, thereby reducing wet adhesion work and preventing the insulator from detaching from the surface of the active coating due to wet adhesion. The larger the particle size, the more obvious the spacing effect, but if it is too large, it will affect ion conduction and easily form electrolyte broken bridges in the later stages of cycling. When the particle size is moderate, it can further improve the purple spot.
[0171] In some embodiments of the present invention, the polymer particles include at least one of acrylate polymers and fluoropolymers, wherein the acrylate polymers do not contain fluorine.
[0172] Among them, acrylate polymers include structural units derived from alkenyl monomers and structural units derived from ester-free monomers;
[0173] The structural unit containing alkenyl monomers includes at least one of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, octyl acrylate, amyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, amyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl acrylate, 2-(diethylamino)acrylate, and 2-hydroxyethyl acrylate.
[0174] The structural units of the ester-free monomers include at least one of styrene, butadiene, ethylene, propylene, methacrylamide, acrylamide, methacrylonitrile, and acrylonitrile;
[0175] Fluoropolymers include at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl fluoride, polyhexafluoropropylene, hexafluoroethylene-hexafluoropropylene copolymer, fluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride-acrylonitrile copolymer.
[0176] Using fluorine-free acrylate polymers in the separator material effectively avoids the environmental compliance risks associated with fluorine-containing substances. Furthermore, these fluorine-free polymers not only possess excellent thermal stability, chemical resistance, and mechanical integrity, but also significantly enhance interparticle cohesion and maintain separator porosity. This ensures dimensional stability under high-rate cycling while substantially improving battery cycle life and overall safety performance.
[0177] In some embodiments, the electrolyte includes, in addition to lithium fluorosulfonate and the compound shown in Formula 1, an organic solvent, a lithium salt, and other functional additives. The organic solvent may be selected from carbonates and / or carboxylic acid esters. Carbonate solvents may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl difluoroacetate, ethyl butyrate (EB), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and fluorinated derivatives of the above solvents. Carboxylic acid ester solvents may be selected from ethyl acetate (EA), propyl acetate, n-butyl acetate, isobutyl acetate, methyl propionate (MP), propyl propionate (PP), ethyl propionate (EP), methyl butyrate, n-ethyl butyrate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropionate, etc. One or more of the fluorinated derivatives of the base ether (D2) and above solvents, and the additives, in addition to Formula 1, include one or more of the following: vinylene carbonate (VC), ethylene ethylene carbonate (VEC), vinyl sulfate (DTD), 1,3-propane sulfonyl lactone (PS), 1,3-propene sulfonate lactone (PST), fluoroethylene carbonate (FEC), tetravinylsilane (TVS), tri(trimethylsilyl)borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), triphenyl phosphite (TPPi), N,N-dimethylaminosulfonyl fluoride or other sulfur-containing oxygen compounds (as shown in Formula (2) below).
[0178] Equation 2.
[0179] Nitrile additives include at least one of the following: mononitrile or dinitrile: benzonitrile, p-toluenenitrile, 3,5-difluorobenzonitrile, adiponitrile (AND), succinic acid (SN), glutaronitrile, octanoic acid, and ethylene glycol bis(propionitrile) ether;
[0180] Nitrile additives with three or more cyano groups include one or more of the following phosphorus-containing trinitrs: 1,3,6-hexanetrionitrile (HTCN), 1,2,6-hexanetrionitrile, glyceryl trinitrile, 1,2,3-tris(2-acryloethoxy)propane, tris(2-cyanoethyl) phosphate, butanetrionitrile, 1,2,3,4,5-penta(2-cyanoethoxy)pentane, ethoxy(pentafluoro)cyclotriphosphazene (PFPN), pentafluoro(phenoxy)cyclotriphosphazene, etc.
[0181] In this application, the lithium salt or lithium salt additive, except for lithium fluorosulfonate, may be selected from electrolyte lithium salts conventionally used in the art, including but not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium 4,5-dicyano-2-trifluoromethylimidazolium (LiDTI), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate), and lithium difluorobis(oxalate borate) (one or more).
[0182] The membrane substrate of the present invention may further include a ceramic coating, wherein the ceramic coating is disposed on at least one side surface of the base membrane, and polymer particles are disposed on the surface of the ceramic coating away from the base membrane and / or on the surface of the base membrane without a ceramic coating.
[0183] To ensure a secure bond between the ceramic coating and the base film, the ceramic coating comprises ceramic particles and a binder. The ceramic particles are selected from one or more of the following: alumina, boehmite, silica, zirconium dioxide, barium sulfate, magnesium hydroxide, fluorapatite, fluorophlogopite, mullite, aluminum titanate, copper oxide, titanium dioxide, and zinc oxide. The binder comprises one, two, or more of the following: polyvinylidene fluoride and polyacrylate.
[0184] The positive electrode active layer of the positive electrode sheet of the present invention comprises, by weight percentage, 80% to 99.8% positive electrode active material, 0.1% to 10% conductive agent, and 0.1% to 10% binder. Preferably, the positive electrode active material layer comprises, by weight percentage, 90% to 99.6% positive electrode active material, 0.2% to 5% conductive agent, and 0.2% to 5% binder.
[0185] The present invention uses at least one of ternary cathode materials and lithium cobalt oxide materials as the positive electrode active material.
[0186] The present invention does not impose any particular limitation on the conductive agent in the positive electrode, which may be selected from the conductive agents commonly used in the art, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene.
[0187] The present invention does not impose any particular limitation on the binder in the positive electrode sheet, which may be selected from binders commonly used in the art, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.
[0188] The negative electrode sheet of this invention includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, a conductive agent, and a binder. The negative electrode active material is selected from graphite or silicon carbide (silicon content 0.1~50%), and the mass percentage of the negative electrode active material in the negative electrode active material layer is 80~98.5 wt%. The conductive agent and binder each account for 0.1~10 wt% of the mass percentage of the negative electrode active material layer. The conductive agent can be selected from at least one of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene. The binder can be selected from at least one of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.
[0189] The lithium-ion battery provided by the present invention will be further described in detail below through specific embodiments.
[0190] Example 1
[0191] The battery preparation method provided in this embodiment includes the following steps:
[0192] 1. Preparation of insulating components:
[0193] The first monomer (butyl acrylate BA), the second monomer (vinyl acetate VAc), and the third monomer (hydroxyethyl acrylate HEA) were mixed in a reactor in a specific ratio. Ethyl acetate was added as solvent (the total amount of solvent was 1.5 times the total amount of monomers). Nitrogen gas was purged, and the mixture was stirred and heated to 75°C. Azobisisobutyronitrile (AIBN) initiator (0.3% of the total amount of monomers) was added, and the reaction was maintained at this temperature for 5 hours. The remaining 40% of the solvent was added, and the temperature was lowered to 30°C (below 40°C). The mixture was stirred until homogeneous, filtered, and the resulting solution was the first polymer solution (solid content approximately 40%). In the first polymer, based on the total weight of the first, second, and third monomers, the mass content of the first monomer was 55%.
[0194] The first polymer solution prepared above is added to the adhesive tank of a microgravure coating machine, transferring the adhesive from the gravure cells to one side of the porous substrate layer, forming an array of dotted adhesive layers. The layer is then dried and cured in a multi-stage, multi-section temperature oven at 80-100℃ at a speed of 25 m / min (curing time 1 min), and finally wound up to obtain the insulating part. The porous substrate layer uses a 9 μm thick PE porous membrane (porosity 45%). Within any 1 mm × 1 mm area of the adhesive layer, the coverage of polymer adhesive dots is 25%, the number of polymer adhesive dots is 30, and the dispersion coefficient of the polymer adhesive dots is A = 25 / 30 = 0.83.
[0195] 2. Preparation of the positive electrode sheet: The positive electrode active material LiCoO2, conductive agent (carbon black: carbon nanotube (mass ratio) = 1:1), and binder polyvinylidene fluoride (PVDF) are dispersed in NMP at a mass ratio of 98.2:0.8:1.0 to form a positive electrode slurry. This slurry is coated onto an aluminum foil safety primer and dried and rolled to obtain a positive electrode active layer with a thickness of 120 μm. A portion of the first surface of the positive electrode bending section is laser-etched to create wire bonding without avoiding voids (the wire bonding size is equal to the width of the positive electrode sheet along the width direction; the average width of the opening end of the first linear recess structure is 100 μm; the distance between adjacent first linear recess structures is 180 μm; and the average depth H2 of the first linear recess structure is 20 μm). Finally, the positive electrode sheet is cut to obtain the positive electrode sheet.
[0196] 3. Preparation of negative electrode sheet: Weigh the negative electrode active material silicon-carbon material (silicon content 48%), conductive agent (carbon black: carbon nanotube (mass ratio) = 1:2), binder (acrylic acid: polyurethane (mass ratio) = 1:5), and thickener sodium carboxymethyl cellulose in a weight ratio of 94.8:0.6:4.0:0.6, disperse them in an appropriate amount of deionized water, stir thoroughly to form a uniform negative electrode slurry, coat the negative electrode slurry onto the negative electrode current collector copper foil, and then dry, roll, and cut to obtain the negative electrode sheet.
[0197] 4. Electrolyte preparation: In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC) / propylene carbonate (PC) / ethyl propionate (EP) / propyl propionate (PP) are mixed evenly at a mass ratio of 10 / 15 / 20 / 55. Then, 14% of fully dried lithium hexafluorophosphate (LiPF6) and 5% lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) based on the total mass of the electrolyte are added. After dissolution, 12 wt% of fluoroethylene carbonate (FEC), 1 wt% adiponitrile (AND), 1 wt% succinate (SN), 2 wt% hexanetrionitrile (HTCN), 5 wt% formula (1-1), 1 wt% lithium fluorosulfonate, and 1 wt%... 1,3-propanesulfonyl lactone (PS) and 0.3wt% lithium difluorooxalate borate (LiODFB) were stirred evenly and, after passing the tests for moisture and free acid, the desired non-aqueous electrolyte was obtained, wherein K=B / A=1.20.
[0198] 5. Separator: Using a gravure coating process, polymethyl methacrylate (PMMA, average particle size 0.85μm) polymer particles are coated on both sides of the separator substrate (including a polyethylene film and a ceramic coating disposed on one side of the polyethylene film). The ceramic coating includes ceramic particles of alumina (Al2O3). After drying, the separator is obtained.
[0199] 6. Assembly of Lithium-ion Batteries: The positive electrode, negative electrode, and separator are placed in sequence, with the separator positioned between the positive and negative electrodes. Then, the electrode tabs are welded and the cells are wound to obtain a core. Along the winding direction, the core includes a bending region, which contains several positive electrode bending sections. Along the thickness direction of the positive electrode sheet, the surface of the positive electrode bending section closest to the winding center of the electrode assembly is the first surface, and the surface of the positive electrode bending section furthest from the winding center of the electrode assembly is the second surface. In a single positive electrode bending section with an insulating element, an insulating element is placed between the first surface and the adjacent separator. There are 5 insulating elements, with one insulating element distributed in each positive electrode bending section. The core is then placed in an aluminum-plastic film packaging bag, followed by processes such as electrolyte injection, formation, secondary sealing, and sorting to prepare a lithium-ion battery. Finally, the battery's electrical performance is tested.
[0200] The preparation methods of the batteries provided in Examples 2-27, Example 29, and Comparative Examples 1-3 are basically the same as those in Example 1, except that the selection of raw material types, the ratio between various substances, and the change of the preparation process of the insulating parts (e.g., at least one of the gravure roller cell parameters, doctor blade pressure, and coating speed) are shown in Tables 1-1 and 1-2, where “ / ” indicates that the substance or data is not available.
[0201] The battery preparation methods provided in Example 28 and Example 1 are basically the same as those in Example 1, except that a portion of the second surface of the positive electrode bending section is laser-etched for wire bonding without avoiding gaps (the wire bonding size is equal to the width of the positive electrode sheet along the width direction). In a single positive electrode bending section with an insulating element, an insulating element is provided between the second surface and the adjacent separator. The resulting batteries are shown in Tables 1-1 and 1-2, where " / " indicates that the material or data is not present.
[0202] Table 1-1
[0203]
[0204] Table 1-2
[0205]
[0206] Test case
[0207] 1. Cyclic performance
[0208] The lithium-ion battery was placed in a 45℃ environment and left to stand for 2 hours. When the battery temperature was 45±2℃, it was discharged at 0.2C to 3.0V; left to stand for 10 minutes; then charged at a constant current of 1.2C to the upper limit voltage (4.53V), then charged at a constant voltage of 4.53V to 0.05C, then discharged at a constant current of 0.5C to 3.0V, and left to stand for 10 minutes; this constitutes one charge-discharge cycle). 500 charge-discharge cycles were performed. The highest discharge capacity of the first 3 cycles was recorded as the initial capacity Q1, and the discharge capacity of the 500th cycle was recorded as Q2. The battery capacity retention rate was calculated as Q2 / Q1×100%. After 500 cycles, the battery was fully charged and disassembled to analyze the purple spot lithium plating.
[0209] The result is represented by "0" when there are no purple spots; "1" when the area of purple spots accounts for less than 3% of the total area of the insulation component; "2" when the area of purple spots accounts for 3%-11% of the total area of the insulation component; "3" when the area of purple spots accounts for more than 11% but less than 20% of the total area of the insulation component; and "4" when the area of purple spots accounts for more than 20% of the total area of the insulation component.
[0210] When there is no lithium plating on the negative electrode side, the result is indicated as "no lithium plating"; when the area of lithium plating on the negative electrode surface accounts for less than 3% of the total area, the result is indicated as "slight lithium plating"; when the area of lithium plating on the negative electrode surface accounts for 3%-11% of the total area, the result is indicated as "significant lithium plating"; when the area of lithium plating on the negative electrode surface accounts for more than 11% of the total area, the result is indicated as "severe lithium plating".
[0211] The test results are shown in Table 2.
[0212] 2. Ratio performance
[0213] The battery was charged and discharged at 25℃ using a battery charge and discharge tester. The charge and discharge regime was as follows: constant current charging at 0.2C to 4.5V, then constant voltage charging at 4.5V until the current decreased to 0.02C, followed by resting for 5 minutes, and then constant current discharging at 0.2C to 2.5V. This cycle was repeated three times, and the average value was recorded as the discharge capacity Q. 0.2c After resting for 5 minutes, charge with a constant current of 0.2C to 4.5V, then switch to a constant voltage of 4.5V and charge until the current decreases to 0.02C. After resting for 5 minutes, discharge with a constant current of 3C to 2.5V. Repeat this cycle three times, take the average value, and record the discharge capacity Q. 3c The capacity retention rate can be calculated using the following formula:
[0214] 3C discharge rate capacity retention rate = Q 3c / Q 0.2c ×100%
[0215] The test results are shown in Table 2.
[0216] Table 2
[0217]
[0218] As shown in Table 2, the battery provided in this embodiment of the invention maintains a capacity retention rate of no less than 71.2% after 500 cycles at 45°C, a capacity retention rate of no less than 63.20% at 3C discharge rate, and exhibits no more than 20% purple spot formation, with no severe lithium plating. This indicates that the battery provided by this invention ensures ion conductivity in the arc region while suppressing electrolyte bridging, purple spot formation, and high-temperature side reactions, thus possessing excellent cycle performance.
[0219] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A battery, characterized in that, It includes a positive electrode, a separator, a negative electrode, an insulating component, and an electrolyte, wherein the positive electrode, the separator, and the negative electrode are stacked and wound to form an electrode assembly; The positive electrode includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector; Along the winding direction of the electrode assembly, the electrode assembly includes a bending region, the bending region includes a plurality of positive electrode bending portions, at least one of the positive electrode bending portions is provided with the insulating member, along the thickness direction of the positive electrode sheet, the surface of the positive electrode bending portion near the winding center of the electrode assembly is a first surface, and the surface of the positive electrode bending portion away from the winding center of the electrode assembly is a second surface. In the single positive electrode bend where the insulating element is provided, the insulating element is provided between the first surface and the adjacent diaphragm, and between the second surface and the adjacent diaphragm; The insulating component includes a porous substrate and an adhesive layer located on at least one surface of the porous substrate, the adhesive layer comprising a plurality of dispersed polymer adhesive dots. The electrolyte comprises lithium fluorosulfonate and a compound of formula 1: Formula 1; R1 and R2 are each independently selected from at least one of alkyl groups having 1-5 carbon atoms, alkenyl groups having 1-5 carbon atoms, and alkynyl groups having 1-5 carbon atoms, whether halogenated or unsubstituted.
2. The battery according to claim 1, characterized in that, The dispersion coefficient of the adhesive layer is A, where A is 0.2~1.5; The dispersion coefficient of the adhesive layer refers to the ratio of the coverage of polymer adhesive dots per square millimeter to the number of polymer adhesive dots per square millimeter.
3. The battery according to claim 2, characterized in that, Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B. K = B / A, where K is between 0.2 and 5.
0.
4. The battery according to any one of claims 1-3, characterized in that, The coverage of the polymer adhesive dots in an area of 10% to 60% per square millimeter; And / or, the number of polymer adhesive dots per square millimeter of the insulating element is 5 to 60; And / or, the porosity of the porous substrate is 25% to 70%.
5. The battery according to any one of claims 1-4, characterized in that, The electrolyte satisfies at least one of the following conditions: (1) Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, where B is 0.5%~5%; (2) Based on the electrolyte, the mass percentage of the compound of formula 1 is C, where C is 2% to 10%; (3) Based on the electrolyte, the mass percentage of lithium fluorosulfonate is B, the mass percentage of the compound of formula 1 is C, R=C / B, and R is 0.5~10.
6. The battery according to any one of claims 1-5, characterized in that, The compound of Formula 1 includes at least one of the compounds with chemical formulas as shown in Formulas 1-1 to 1-7: Equation 1-1, Equation 1-2, Equation 1-3, Equation 1-4, Equation 1-5, Equations 1-6 Equations 1-7.
7. The battery according to any one of claims 1-6, characterized in that, At least a portion of the first surface includes a first region, at least a portion of the first region is covered by the insulating element, and the first region is provided with a first linear recessed structure. The first linear recessed structure satisfies at least one of the following conditions: (1) The average width of the opening end of the first linear recessed structure is 50 μm to 150 μm; (2) The distance between adjacent first linear recessed structures is 100μm~350μm; (3) The thickness of the positive electrode active layer is H1, the average depth of the first linear recess structure is independently H2, and H2 / H1 is 0.1~0.6; preferably, H1 is 50μm~150μm and H2 is 5μm~50μm; (4) Along the width direction of the positive electrode, the size of the first region is equal to the width of the positive electrode.
8. The battery according to any one of claims 1-7, characterized in that, At least a portion of the second surface includes a second region, at least a portion of the second region is covered by the insulating element, and the second region is provided with a second linear recessed structure; The second linear recessed structure satisfies at least one of the following conditions: (1) The average width of the opening end of the second linear recessed structure is 50 μm to 150 μm; (2) The distance between adjacent second linear concave structures is 100μm~350μm; (3) The thickness of the positive electrode active layer is H1, the average depth of the second linear recess structure is H3, and the ratio of H3 to H1 is 0.1 to 0.6; preferably, H1 is 50 μm to 150 μm and H3 is 5 μm to 50 μm. (4) Along the width direction of the positive electrode, the size of the second region is equal to the width of the positive electrode.
9. The battery according to any one of claims 1-7, characterized in that, The diaphragm includes a diaphragm matrix and polymer particles disposed on at least a portion of the surface of the diaphragm matrix.
10. The battery according to claim 9, characterized in that, The average particle size of the polymer particles is 0.3 μm to 3 μm; And / or, the polymer particles include at least one of acrylate polymers and fluoropolymers, wherein the acrylate polymers do not contain fluorine.